Analisis Bahasa Persuasi yang Disertai Iming – Iming dalam Promosi Judi Online - Chalfina Egy Noviana; Devina Agustina (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2026)
Language is a communication tool that has an important role in conveying information, ideas, and influencing others. In promotional activities, persuasive language is often used to attract public interest, including in online gambling activities. Online gambling cases in Indonesia are also increasingly prevalent with 3.1 million users and fund turnover reaching Rp 1,032 trillion until the third quarter of 2025 (PPATK). Online gambling promotions often use persuasive language accompanied by lures such as the promise of big profits, ease of getting money, and various guarantees to attract the interest of potential players. This study aims to analyze the use of persuasive language accompanied by lures in online gambling promotion. The method used is qualitative descriptive with data collection techniques in the form of in-depth interviews with five key informants, literature studies, and documentation. The results of the study show that online gambling promotions use a lot of persuasive language accompanied by lures to attract attention and influence others, such as "capital makes a little profit many times", "100% balance back guarantee", one spin makes tajir", "register now immediately gacor", and "anti-rungkat site". The strategy emphasizes the aspects of ease of winning, guaranteed instant profits, and the site's trust to influence the victim. These findings suggest that the use of persuasive language in online gambling promotions has the potential to influence people's self-esteem by creating false expectations and ignoring the real risks.